2013
DOI: 10.1149/2.045312jes
|View full text |Cite
|
Sign up to set email alerts
|

Resistivity Reduction in Very Narrow Cu Wiring

Abstract: Low resistivity 60 nm wide Cu wires were realized by the combination of lessening impurities through additive-free plating using high-purity plating materials and high-heating rate annealing. Resistivity values of Cu wires made with the new method were about 14% lower than those made by conventional plating with additives and high-heating rate annealing at the same temperature. The resistivity values were also found to be more than 50% lower than those for Cu wires made by plating with additives using low-puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The discrepancy of the increase ratio of the grain diameter between the simulation and the actual experiment can be attributed to impurity atoms. In the previous research, we analyzed by glow discharge mass spectrometry (GDMS) the impurities in Cu films formed by plating with and without additives using high-purity and low-purity plating materials [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The discrepancy of the increase ratio of the grain diameter between the simulation and the actual experiment can be attributed to impurity atoms. In the previous research, we analyzed by glow discharge mass spectrometry (GDMS) the impurities in Cu films formed by plating with and without additives using high-purity and low-purity plating materials [13].…”
Section: Discussionmentioning
confidence: 99%
“…The result showed that the total impurities in Cu films were decreased clearly by using the high purity plating materials. Especially, the amount of impurities like O, C, Cl, Ti and Fe, which may suppress grain growth during annealing, were reduced (see Table I in reference [13]). Resistivities as a function of holding time at the peak temperature for the 60 nm wide Cu wires made with additive-free plating using high-purity plating materials (6N electrolyte/8N anode process) and high-heating rate annealing at 1.7 K/s were also measured (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental for evaluation of electrical resistivity and grain size.-We used a four-point probe method 15 and field emission transmission electron microscope (FE-TEM) observations respectively to measure electrical resistivity and grain size in the Cu wires. We fabricated Cu wire structures including Fe impurity as follows.…”
Section: Measurement and Calculation Methodsmentioning
confidence: 99%